A customizable cost-effective design for printed circuit board-based nanolayered gold screen-printed electrode: From fabrication to bioapplications - Ghorbanzadeh, Sadegh; Naghib, Seyed Morteza; Sadr, Ali; Molaabasi, Fatemeh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Screen-printed electrodes (SPEs) are promising candidates for fabricating biosensing platforms in the laboratory and industry due to the various advantages they involve. The primary method for fabricating SPEs is 2D printing. However, commercial SPEs have some limitations due to the specific ports and connections they require, inflexible design, high prices, and decreased efficiency after a short time. This article introduces high performance, feasible, and cost-effective gold SPEs based on the combination of printed circuit board substrate (PCBs) and sputtering methods for electrochemical biosensing platforms. First, we discuss a general gold SPE development procedure that helps researchers to develop specific designs. The final developed version of SPEs was characterized in the second step, showing positive performance in electrochemical parameters because of the optimization of design and fabrication steps. In the study’s final phase, SPEs were used to fabricate a simple platform for breast cancer cell detection as a proof of concept without using any linker or labeling step. The designed immunosensor is very simple and cost-effective, showing a linear calibration curve in the range of 10 − 2× 102 cells mL−1 (R2 = 0.985, S/N = 3). This research can be used as a reference for future studies in SPEs-based biosensors because of the flexibility of its design and the accessibility of the manufacturing equipment required.